The Effect of Tax Socialization, Tax Knowledge, Expediency of Tax ID Number and Service Quality on Taxpayers Compliance with Taxpayers Awareness as Mediating Variables. (25th November 2015) - Andreas; Savitri, Enni
Abstract: The purpose of this study is to examine the mediating role of taxpayers awareness of the relationship among tax socialization, tax knowledge, expediency of tax id number, service quality and taxpayers compliance. A survey was conducted on 100 taxpayers registered in the Pekanbaru-Senapelan tax office. Data analysis was using path analysis. The result shows that taxpayers awareness has a full mediating role in the relationship between expediency of tax id number, service quality, and taxpayers compliance. Conversely, taxpayers awareness has no mediating role in the relationship between tax socialization, tax knowledge, and taxpayers compliance. Implication of these findings will be discussed.